Penerapan Terapi Psikoreligius : Dzikir pada Pasien Halusinasi Pendengaran di Rumah Sakit Jiwa Daerah (RSJD) Dr. Arif Zainudin Surakarta - Siti Sundari; Norman Wijaya Gati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Hallucinations are a mental disorder in which clients experience disturbances in perception, sensory, taste, touch, sight or smell. Auditory hallucinations are where clients hear voices commanding and calling them to carry out activities in the form of two or more voices commenting on a person's behavior or thoughts. (Abdurakhman & Maulana, 2022). According to WHO (World Health Organization, 2020) there are 300 million people worldwide experiencing mental disorders such as depression, bipolar disorder, dementia, including 24 million people experiencing schizophrenia. Schizophrenia is one of the 15 major causes worldwide. APA data (American Psychiatric Association, 2020) states that 1% of the world's population suffers from schizophrenia. (Dwijayanti, 2022). In this study, the way to see the increase in the ability to control hallucinations is by using the AHRS scale which is used to measure auditory hallucination scores. To determine the results of applying dhikr psychoreligious therapy to patients with auditory hallucination disorders. Applying dhikr psychotherapy therapy using a descriptive case study method for 2 respondents for 2 years. consecutive days. The instrument used was the Auditory Hallucinations Rating Scale. Results: Based on the results of applying psychoreligious dhikr therapy to 2 respondents, there was a decrease in the symptoms of auditory hallucinations in patients. Psychoreligious dhikr therapy can be used as an implementation of independent nursing to control and overcome the emergence of hallucinations.